Current Perspective of Plant-Based Diets on Communicable Diseases Caused by Viruses: A Mini Review - Wong, Carisa Su-Ann; Lim, Cheng Wei; Mohammed, Haruna Isa; Liew, Kong Yen; Tham, Chau Ling; Tan, Ji Wei; Chee, Hui Yee (Frontiers in Nutrition, 2022)
Communicable diseases are illnesses caused by pathogenic biological agents including viruses, bacteria, fungi, parasites and protozoa. The diseases spread from people to one another through contact with contaminated surfaces, bodily fluids, blood products, through the air, insect bites or consuming contaminated food and beverage. Although some of these communicable diseases can be treated or prevented by taking medication and vaccines, there has been an increase in awareness of adopting a healthful diet to aid in the prevention and reversal of these diseases. One of the popular diets is the plant-based diet. Plant-based diet generally includes mostly of vegetables, grains, nuts, seeds, legumes, and fruits without any animal-source foods or artificial ingredients. Over the years, this diet has continuously increased in its popularity. Reasons for following a plant-based diet are varied but include health benefits, such as improving immunity, reducing the risk of heart disease, diabetes and some cancers. There is even scientific evidence that shows just an increase in vegetarian diet intake can decrease the occurrence of chronic diseases caused by viruses such as hepatitis viruses, and reducing the risk of severe COVID-19. Therefore, this mini review will discuss the effectiveness of adopting a plant-based diet in ameliorating the disease caused by selected viruses and the limitations.